Uncovering value creation factors for healthcare public-private partnership (PPP) projects - Budayan, Cenk; Koc, Kerim; Erk, Eralp Yuksel; Tokdemir, Onur Behzat (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeMany countries struggled to respond to the pandemic burden; in fact, most suffer from healthcare incapacity generally. Therefore, they need to find innovative systems to compensate for their deficiencies in dealing with current and future problems. One such goes down the public-private partnership (PPP) route. It is important to note, however, that PPP is not a magic wand, and some of these projects have been criticized for overruns that exceed the value created. Aiming to promote the value created in healthcare PPP projects, this study aims to identify factors and critical points related to their implementation.Design/methodology/approachA two-stage literature review was conducted to shape semi-structured interviews. Based on this, the questions to be asked in the interviews were prepared. The interviews were conducted with twelve experts. The transcripts of the twelve semi-structured interviews were analyzed using manual thematic analysis to reveal the most critical value-creation factors (VCFs). The VFCs were validated by comparing them with the studies in the literature and by having focus group discussions (FGDs) with the experts. Finally, in an FGD, the experts discussed how these factors affect value creation in healthcare PPP projects.FindingsThe findings show that VFCs can be categorized into four dimensions: assets, partnership synergy, cooperation environment and processes. Based on the frequency of codes during the thematic analysis, the most frequently addressed VFCs in each category were identified. These were complementary skills and resources, attitude, early establishment of the operational body and effective design development, respectively.Practical implicationsThis research contributes to both society and practice by unveiling VCFs and effective ways to achieve them in healthcare PPP projects. Thus, practitioners can generate more value and bring value to the forefront of healthcare PPPs, which can then enhance the value gained by society.Originality/valueStudies to date have offered little about VCFs and how to realize value in PPP projects by considering the factors involved in them. Moreover, value creation in PPP healthcare projects has largely remained unexplored, despite PPPs being adopted and investigated quite commonly.
Keywords: Value in construction; Value creation factors; Public-private partnerships (PPPs); Healthcare sector; CRITICAL SUCCESS FACTORS; TARGET VALUE DESIGN; VALUE CAPTURE; MANAGEMENT; PERFORMANCE; STAKEHOLDERS; FRAMEWORK; DELIVERY; MODELS; RISK; Engineering; Business & Economics